Scientific profiles in the field of children obesity - Biglu, Mohammad-Hossein; Ghavami, Mostafa (Revista Cubana de Información en Ciencias de la Salud, 2016)
Childhood obesity is a serious health issue that has both immediate and long-term effects on health and well-being. Although obesity affects both children and adults, but childhood obesity is more serious than obesity in adults. The objective of current study was to depict the trend of publication entitled pediatric obesity indexed in the database of Scopus during years 2001-2015. A bibliometrics study was conducted to plot the development of scientific activities in the field of Pediatric obesity. Database of Scopus which covers 100 % of MEDLINE was used to extract all papers entitled pediatric obesity for a period of 15 years. Extraction of papers was restricted into papers entitled "pediatric obesity" from the Search Builder pull-down menu in the advanced search screen, this causes to obtain the articles that their major topics are in the desired subject area. Analysis of data showed that a total number of 663 papers entitled pediatric obesity indexed in scopus during the period of study. The results of study specified the investigation of pediatric obesity in 18 subject areas; the subject area of psychology seems to be in the inferior concern of scientists. Regarding the important influence of socio-psycho-genetic aspects on the pediatric obesity, these issues of study should be taken under consideration by policy-makers and nutritional scientists.